Le cellule staminali mesenchimali nel trattamento delle condropatie del ginocchio - Grazioli, A.; Scaravilli, G.; Di Maggio, F.; Bove, G.; Italiano, M.; Pezone, R.; Di Maggio, B. (Lo Scalpello - Journal, 2019)
MESENCHYMAL STEM CELLS IN THE TREATMENT OF KNEE CHONDROPATHIES Osteoarthritis (OA) is the most common joint pathology and it is responsible, in the elderly, for a number of cases of disability higher than those caused by other situations. In last years, “regenerative” treatment techniques for cartilage tissue have met with a broad consensus in orthopaedics. For some time, the function of adipose tissue has been re-evaluated as a real endocrine organ, from which the Stromal Vascular Fraction (SVF) is obtained through specific treatments. It contains the mesenchymal adipose stem cells (AdMSC), which are “multipotent” stem cells. For about 10 years, the use of these cells in the treatment of early osteoarthritis has begun in human medicine, thanks to studies that have shown, among other things, the ability of these cells to regenerate hyaline cartilage.